Fabrication of Gold Nanoflower-Coated Photosensitive Meta-Structures Using PμSL 3D Printing for Hyperthermia Applications - Ersoy, Serra; Yildiz, Erdost; Ren, Ziyu; Zhang, Mingchao; Zhang, Hongchuan; Karaz, Selcan; Han, Mertcan; Shiva, Anitha; Yunusa, Muhammed; Kaya, Cengiz; Koc, Bahattin; Sitti, Metin (AMER CHEMICAL SOC, 2024)
The objective of this work was to print nanoparticle-added photothermoresponsive hydrogels to remove the drawbacks of photothermal therapy (PTT), which is a substitute for conventional cancer treatment. For printing hydrogels (LIHAM) via N-isopropylacrylamide (NIPAM), polyethylene glycol, green synthesized gold nanoflowers (AuNPs) coated with rose bengal (RB) as a photosensitizer, and polydopamine (PDA) as photoinitiator material were used. The printing procedure for the meta-structure, which was designed as 20 x 2 mm using the 3DS Max Autodesk Software, was carried out with the microArch S240 BMF P mu SL 3D printer. Additionally, the intensity of light was 60 lm, and the exposure printer time was 8-6-6-6-4 s for this research article. Five different photosensitive hydrogels were printed for rheological measurements, Fourier-transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, differential scanning calorimetry, and hyperthermia analysis. This study also aims to demonstrate that the kirigami LIHAM hydrogel can change shape by doping with AuNPs@PDA@RB exclusively under 565 nm without the need for a heater. The results indicated that the greatest outcomes in terms of mechanical, rheological, chemical, and thermal properties and printability were obtained with LIHAM hydrogels coated with AuNPs@PDA@RB. As a result, it has been seen that the LIHAM hydrogels coated with green synthesized gold nanoflowers can be produced with a 3D printer in microsized and complex structures and can be used in hyperthermia applications in the future.
Keywords: transition metal nanoparticles; green synthesis; kirigami; rose bengal; polydopamine; ROSE-BENGAL; NANOPARTICLES; Materials Science; Polymer Science